AN ANALYSIS OF THE ASPECTS OF HEALTHCARE SERVICE QUALITY IN RELATION TO PATIENT LOYALTY - Dwita Aryadina Rachmawati (UPT Penerbitan Universitas Jember)
Healthcare facilities such as hospitals, public healthclinics, and private practices are places that peoplevisit to obtain thorough medical care. The state billno.44 of 2009 stipulates that hospitals areinstitutions that provide complete healthcare servicefor individuals. The service included is providinginpatient facilities, home care, and medicalemergency service. According to the bill, among thefunctions of a hospital is to establish and maintainthe quality standard of healthcare service within thehospital, which is then used as a blueprint or areference in day to day patient care.The general public are becoming evermoreconscientious on choosing which hospital to go towhen they become ill. Which is why for everyhospital that offers medical service, the challengethen arises on how to implement various strategiesin order to develop and not merely survive in thegrowing healthcare industry. Among the strategiesthat needs attention is sustaining the qualitystandard of the hospital care service.The quality standard of the hospital care service canbe measured using the SERVQUAL model (ServiceQuality model), which gives rate to the indicators ofvarious qualities of service (Tjiptono, 2011). Thereare 5 main aspects that are measured and arrangedbelow according to the relativesignificance/importance (Tjiptono dan Chandra,2011):A. Reliability, which signifies the institution's abilityto provide error-free and accurate medical careupon patient arrival, within the agreed upon timeconstraint.B. Responsiveness, signifies the healthcarepersonnel's availability and capability to provide fastresponse aid and cater to their needs and request. Italso involves the tactful knowledge of informing thepatient when the medical care will be given andperforming the promised care accordingly.C. Assurance, signifies how the healthcare personnelestablish trust with patients which in turn earns thepatient's trust towards the institution. This can beachieved by providing healthcare personnel whomaintain courteous conduct at all time yet possessthe skill and ability to answer any arising questionsor handle any given situation.Furthermore, it involves the institutions ability tofoster a safe and secure environment for patients.D. Empathy, signifies the ability of healthcarepersonnels to establish effective communicationwhile delivering proper diagnosis. Caring is anessential component which can be implemented bygiving personal attention to each patient.E. Tangibles, correlates with the physicalenvironment of the establishment, which can comein the form of an attractive office design, availabilityof a full range medical equipment, and furthercomplemented by the pleasant appearance of thehealthcare personnels.Delivering optimum service is essential forinstitutions who thrive on gaining customersatisfaction and building towards patient loyalty inthe long run.